Dietary counseling outcomes in locally advanced unresectable or metastatic cancer patients undergoing chemotherapy - Napawan Sukaraphat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Background: Cancer-related malnutrition led to poor outcomes of treatment, decreased functional status, decreased quality of life, and delay treatment. Objective: To examine the effects of dietary counseling for regular foods consumption on nutritional outcomes in patients with cancer undergoing chemotherapy. Material and Method: A prospective randomized study was performed on locally advanced unresectable or metastatic cancer patients undergoing chemotherapy at Department of Medicine, Chiang Mai University, between December 2013 and July 2014. Fifty patients were randomly assigned to dietary counseling group and routine care group. The dietary counseling was performed by a dietitian before starting chemotherapy. Outcomes were evaluated at the end of three to four cycles and six to eight cycles of chemotherapy or after two months if the chemotherapy was stopped earlier. Results: The dietary counseling group significantly increased percent change of body weight 2.29 (±6.20) vs. -1.70 (±6.23) percent in the routine care group, p = 0.03 and increased BMI 2.27 (±6.09) vs. -1.53 (±5.92) percent, p = 0.03 at the end of three to four cycles of chemotherapy, but there was no significant change at the next two months. Furthermore, PG-SGA score was lower in the dietary counseling group (6.67 (±1.99) vs. 10.04 (±3.73), p<0.001, and quality of life was significant increased in dietary counseling group at the end of three to four cycles of chemotherapy and at the next two months (score 39.40 (±10.61) vs 46.16 (±7.55), p = 0.01). Absolute lymphocyte count, serum albumin, energy intake, number of patients who delayed chemotherapy, cause of delay chemotherapy, and number of total cycles did not differ between the groups. Conclusion: Dietary counseling have significantly improved body weight, BMI, PG-SGA scores, and quality of life scores in patients with locally advanced unresectable or metastatic cancer undergoing chemotherapy compared with routine care. We should be concerned about screening for malnutrition in all cancer patients and we should provide nutritional counseling.